2020
DOI: 10.1177/2055102920954710
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of older adults in nursing homes in Vietnam

Abstract: This study evaluated the quality of life of older adults in Vietnam. A survey was conducted on 291 old people at eight public and private nursing homes using cluster sampling. Quality of life was predicted by gender, duration of stay, center activities and community tangible support, and connection with family. Results were consistent across the four subscales of the Quality of Life Index. Quality of life of Vietnamese older adults depends not only on the quality of services provided by the nursing homes but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
1
10
0
1
Order By: Relevance
“…However, older people mainly receive support from family members and live with them. Financially affordable facilities and services are insufficient in many of these countries (e.g., Asian Development Bank, 2020a, 2020b; Dissanayake, 2014; Dung et al, 2020; Ga, 2020; Loy, 2012; Sumini et al, 2020). This list of old‐age pension schemes may not be exhaustive, but it includes the major old‐age pension schemes and benefits in the selected countries.…”
Section: Childrearing and Care In Asiamentioning
confidence: 99%
“…However, older people mainly receive support from family members and live with them. Financially affordable facilities and services are insufficient in many of these countries (e.g., Asian Development Bank, 2020a, 2020b; Dissanayake, 2014; Dung et al, 2020; Ga, 2020; Loy, 2012; Sumini et al, 2020). This list of old‐age pension schemes may not be exhaustive, but it includes the major old‐age pension schemes and benefits in the selected countries.…”
Section: Childrearing and Care In Asiamentioning
confidence: 99%
“…The results of research conducted by Dung et. al (2020) towards 291 elderly living in nursing homes in Vietnam showed that the quality of life of the elderly is at a moderate level (12).…”
Section: Results and Discusionmentioning
confidence: 99%
“… 22 In line with Vietnamese culture which emphasizes family relationships, it is possible to establish regular communication between family members as the key to parental happiness. 22 In contrary, in Indonesia the majority of the elderly who are living in PSTW were in a poor condition, felt lonely, had no family members who could take care of them, and did not have a house to live in. Therefore, they are living on streets as beggars, so the police officer from the Social Department took these displaced elderly to live in PSTW.…”
Section: Discussionmentioning
confidence: 99%